2019
DOI: 10.3390/f10070571
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Traditional Livelihood Practices and Local Ethnobotanical Knowledge in Mitigating Chestnut Disease and Pest Severity in Turkey

Abstract: The European chestnut population is enduring multiple compounding exotic pest and disease outbreaks across Turkey. The deeply held value of the chestnut species for the Turkish public is reflected in substantial government conservation programming. Chestnut is predominantly found on state land managed by Turkey’s General Directorate of Forestry (GDF), which generally upholds restrictive policies for chestnut-related livelihood practices other than nut collection and beehive placement. Such policies are justifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Multilevel models integrate different structures for random effects such as individual, crossed and nested structures as well as various types of models accounting for different levels of complexity including a random intercept, random slope, and both random intercept and slope models. For example, a nested random effect could arise from establishing plots as nested in sites (Wall et al ., 2019) or from genera nested within a given plant family (Bebber et al ., 2007). Another example is related to testing the theory of non‐random medicinal plant selection (Moerman, 1979; Ford & Gaoue, 2017; Robles Arias et al ., 2020; Muleba et al ., 2021).…”
Section: Advanced Statistical Methods For Hypothesis Testing In Ethno...mentioning
confidence: 99%
“…Multilevel models integrate different structures for random effects such as individual, crossed and nested structures as well as various types of models accounting for different levels of complexity including a random intercept, random slope, and both random intercept and slope models. For example, a nested random effect could arise from establishing plots as nested in sites (Wall et al ., 2019) or from genera nested within a given plant family (Bebber et al ., 2007). Another example is related to testing the theory of non‐random medicinal plant selection (Moerman, 1979; Ford & Gaoue, 2017; Robles Arias et al ., 2020; Muleba et al ., 2021).…”
Section: Advanced Statistical Methods For Hypothesis Testing In Ethno...mentioning
confidence: 99%
“…These families are generally not in a position to afford substitutes [4,19]. Farmers often use agrobiodiversity to manage risks because of limited access to agricultural inputs, such as pesticides, fertilizers, and irrigation systems [5,[20][21][22][23][24]. The use of diverse sets of crop varieties and livestock breeds has ensured sustainable production under conditions of unpredictable rainfall patterns, droughts, storms, and floods [4].…”
Section: Introductionmentioning
confidence: 99%
“…In these contexts, decision-making is likely to be reactive and based on experience. Wall et al [8] provide another perspective on forest governance with the example of local land managers in Turkey who grow chestnut (Castinea sativa) facing opposition to their practices on state-owned land [8]. Investigations by the authors found that traditional land management practices positively contributed to healthy chestnut populations, but these practices are treated with suspicion by state authorities.…”
Section: Introductionmentioning
confidence: 99%
“…Differing risk perceptions have led forest authorities to believe that human activity in the forests is negative instead of considering the positive roles that people play in maintaining forest health as part of their livelihood practices. Risk perceptions around practices such as grafting to increase commercial chestnut production have, according to Wall et al [8], impeded the growth of multipurpose community forest initiatives. They call for greater inclusion of local knowledge in forest management thinking and emphasise the contribution of traditional practice to creating resilient forests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation